Semiconducting boron carbides with better charge extraction through the addition of pyridine moieties. (4th August 2016) - Echeverria, Elena; Dong, Bin; Peterson, George; Silva, Joseph P; Wilson, Ethiyal R; Driver, M Sky; Jun, Young-Si; Stucky, Galen D; Knight, Sean; Hofmann, Tino; Han, Zhong-Kang; Shao, Nan; et al.
Abstract: The plasma-enhanced chemical vapor (PECVD) co-deposition of pyridine and 1, 2 dicarbadodecaborane, 1, 2-B10 C2 H12 (orthocarborane) results in semiconducting boron carbide composite films with a significantly better charge extraction than plasma-enhanced chemical vapor deposited semiconducting boron carbide synthesized from orthocarborane alone. The PECVD pyridine/orthocarborane based semiconducting boron carbide composites, with pyridine/orthocarborane ratios 3:1 or 9:1 exhibit indirect band gaps of 1.8 eV or 1.6 eV, respectively. These energies are less than the corresponding exciton energies of 2.0 eV–2.1 eV. The capacitance/voltage and current/voltage measurements indicate the hole carrier lifetimes for PECVD pyridine/orthocarborane based semiconducting boron carbide composites (3:1) films of 350 µ s compared to values of ⩽35 µ s for the PECVD semiconducting boron carbide films fabricated without pyridine. The hole carrier lifetime values are significantly longer than the initial exciton decay times in the region of 0.05 ns and 0.27 ns for PECVD semiconducting boron carbide films with and without pyridine, respectively, as suggested by the time-resolved photoluminescence. These data indicate enhanced electron–hole separation and charge carrier lifetimes in PECVD pyridine/orthocarborane based semiconducting boron carbide and are consistent with the results of zero bias neutron voltaic measurements indicating significantly enhanced charge collection efficiency.